BIOLOGICAL CHARACTERISTICS OF REPRODUCTION OF FRUIT AND BERRY PLANTS - Usmonov Saminjon Olimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Blueberries and berries are rich in substances necessary for the human body. They contain carbohydrates, acids, minerals, vitamins, additives, pectin and flavoring substances. Some of them, for example, in nuts, also contain protein and fat. Fruits and berries have a pleasant taste and smell, which is easily digested by the body of a person. In this article, we will talk about similar fruits and ways of multiplying them.